1990
DOI: 10.1038/ki.1990.329
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of dialysis-related amyloid (AB-amyloid) deposits with 131I-β2-microglobulin

Abstract: The diagnosis of dialysis-related amyloid (AB-amyloid) has been based usually on clinical and radiological criteria. Following the discovery that beta 2-microglobulin was the major protein of this amyloid, we isolated and radiolabelled uremic plasma beta 2-microglobulin. After intravenous injection, gamma-camera images of selected joint areas were obtained from 42 patients who were on regular hemodialysis therapy. Positive scans involving the shoulder, hip, knee and carpal regions were found in 13 of 14 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 21 publications
2
44
1
1
Order By: Relevance
“…An alternative to scanning with radiola belled serum amyloid P component is of fered by the injection of radiolabelled hu man (32-microglobulin [38,39], Using this technique, we were able to detect local tracer accumulations, confined to articular and periarticular sites, in 23 of 42 chronic hemo dialysis patients ( fig. 1) examined.…”
Section: Radiodiagnostic Approachesmentioning
confidence: 98%
“…An alternative to scanning with radiola belled serum amyloid P component is of fered by the injection of radiolabelled hu man (32-microglobulin [38,39], Using this technique, we were able to detect local tracer accumulations, confined to articular and periarticular sites, in 23 of 42 chronic hemo dialysis patients ( fig. 1) examined.…”
Section: Radiodiagnostic Approachesmentioning
confidence: 98%
“…Because of the high prevalence o f cystic lesions in the patients with CTS as a complication and the deposits o f amyloid matching the localization o f B2M in 10 speci mens o f bone cysts, it appears that the cystic radiolucencies may be related to dialysis-associated amyloidosis, with B2M ll as the precursor protein. Floege [22] recently showed that the whole body scanning method using radiolabelled B2M may be useful in evaluating dialysis-associated amyloid osis. Our method for staging the disease, although limited to the wrist joint, is easy to perform and could be useful in classifying the severity o f the dialysis-associated amyloid osteoarthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…After this time there is an almost linear increase of the prevalence, which reaches nearly 100% after 20 years of treatment [7,8,28,58] (ta ble 1). When patients are evaluated by the more specific and sensitive diagnostic method of l31I-p2-microglobulin scintigraphy [80,81], an even more rapid increase of the prevalence of Ap2M amyloidosis in chronic hemodialysis patients is detected (table 1).…”
Section: Prevalence O F a [Hm A Myloidosismentioning
confidence: 99%
“…Clinically, two risk factors for AfTM amyloid deposi tion have been identified: age at onset of renal replace ment therapy [28,85] and the duration of (nontransplant) renal replacement therapy [7,8,28,56,58,81,85], Other factors, such as hyperparathyroidism, extraosseous calci fications [75,86] as well as aluminum [87,88] or iron overload [16,89] have also been suggested to represent risk factors for AP2M amyloid deposition. However, the relevance of these latter factors has to remain speculative, as it cannot be excluded that A(TM amyloid deposition and, for example, iron overload represent independent events, both of which are related to the duration of renal replacement therapy.…”
Section: Risk Factors For Afom Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation